URGENSI PENGATURAN TRADE DRESS DALAM PERLINDUNGAN MEREK TERKENAL SERTA IMPLIKASINYA TERHADAP PERSAINGAN USAHA - Al Qawiy, Ifin Rizky; Gultom, Alif Muhammad (JIPRO: Journal of Intellectual Property, 2024)
The rise of trade dress imitation cases involving well-known trademarks in Indonesia reveals a regulatory gap that potentially harms legitimate businesses and misleads consumers. This article explores the urgency of regulating trade dress within the framework of intellectual property protection, particularly for well-known trademarks that are frequently targeted by visual imitation. Using a normative approach and analyzing Supreme Court Decision No. 402 K/Pdt.Sus/2011, this research highlights the shortcomings of Indonesia’s legal instruments in providing comprehensive protection for non-verbal visual identities, which play a vital role in brand differentiation and reputation. The study also compares Indonesia’s approach with international standards and identifies the need for regulatory harmonization to close legal loopholes exploited for unfair competition. The findings recommend that the concept of trade dress should be explicitly recognized and regulated in Indonesian law to strengthen legal certainty, protect consumers, and uphold fair business competition.